Methyl methacrylate copolymer composition for injection molding

By adjusting the usage ratio of recovered methyl methyl propionate and adding specific copolymers, the problems of slowing polymerization rate and silver stripes caused by the Tromsdorf effect are solved, and the efficient polymerization of the resin and good injection molding performance are achieved.

JP2025054556APending Publication Date: 2025-04-08ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023163667
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When polymerization is performed using recovered methyl methyl methyl propionate, the Tromsdorf effect does not occur, resulting in slowing down the polymerization rate and increasing the remaining units, forming a heat-resistant methyl methyl propionate resin, which occurs silver stripes, affecting the performance of injection molding.

Method used

By adjusting the use ratio of recovered methyl methyl propionate and adding copolymers such as methyl isobutyric acid and 2- or 3-heptene to the resin, the content of the copolymer is controlled between 1-1500 ppm and 10-2000 ppm to prevent the polymerization rate from slowing down.

Benefits of technology

It effectively prevents the slowdown of the polymerization rate, suppresses the formation of silver stripes, and improves the thermal stability and injection molding performance of the resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054556000001_ABST
    Figure 2025054556000001_ABST
Patent Text Reader

Abstract

To provide a methyl methacrylate copolymer composition for injection molding capable of preventing stall of polymerization even when recycled methyl methacrylate is used, further suppressing silver streaks generation during injection molding.SOLUTION: A methyl methacrylate copolymer composition for injection molding of the present invention is a methyl methacrylate copolymer composition that contains a methyl methacrylate copolymer obtained by polymerizing a monomer composition containing 10 to 50 mass% of recycled methyl methacrylate and 50 to 90 mass% of non-recycled methyl methacrylate. A content of methyl isobutyrate in the methyl methacrylate copolymer composition is 1 to 1500 mass ppm, and the content of 2-heptene and / or 3-heptene in the methyl methacrylate copolymer composition is 10 to 2000 mass ppm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an injection molding composition containing a methyl methacrylate copolymer. [Background technology]

[0002] In order to reduce the environmental impact, research is being conducted into "chemical recycling," in which polymethyl methacrylate is thermally decomposed and depolymerized to isolate and reuse the methyl methacrylate. For example, Patent Document 1 describes a method for thermally decomposing polymethyl methacrylate (PMMA, polymethyl methacrylate). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2022-520072 Summary of the Invention [Problem to be solved by the invention]

[0004] Usually, when suspension polymerization or bulk polymerization is carried out using methyl methacrylate, the diffusion rate of growing radicals at the polymer end decreases due to an increase in viscosity in the later stage of polymerization, which makes it more difficult for termination reactions due to collisions between radicals to occur than in the early stage of polymerization, and as a result, the growing reaction proceeds more easily and the polymerization rate increases. This is called the Trommsdorff effect. The increase in polymerization rate due to the Trommsdorff effect can improve the polymerization conversion rate and reduce residual monomers. However, when attempting to polymerize using recycled methyl methacrylate, the Trommsdorff effect does not occur, i.e., polymerization does not accelerate, and a problem occurs in that the phenomenon of an increase in residual monomers frequently occurs. Methacrylic resins with a large amount of residual monomers are not actively used for injection molding applications due to issues such as poor heat resistance and the occurrence of silver streaks during injection molding. As a result, there is a problem that the use of recycled methyl methacrylate and its social implementation have not progressed. [Means for solving the problem]

[0005] In order to solve the above problems, the present inventors conducted extensive research and surprisingly found that by adjusting the amount of recycled methyl methacrylate used and polymerizing the copolymer so that the amounts of methyl isobutyrate and 2-heptene and / or 3-heptene in a resin composition containing the copolymer are within optimal ranges, it is possible to prevent polymerization stall due to the failure to exhibit the Trommsdorff effect during polymerization and further to suppress the occurrence of silver streaks during injection molding, thereby completing the present invention.

[0006] That is, the present invention is as follows. [1] 10 to 50% by mass of recycled methyl methacrylate, 50-90% by mass of non-recycled methyl methacrylate, A methyl methacrylate copolymer composition comprising a methyl methacrylate copolymer obtained by polymerizing a monomer composition containing The content of methyl isobutyrate in the methyl methacrylate copolymer composition is 1 to 1500 ppm by mass, The content of 2-heptene and / or 3-heptene in the methyl methacrylate copolymer composition is 10 to 2000 ppm by mass. Methyl methacrylate copolymer composition for injection molding. [2] The methyl methacrylate copolymer composition for injection molding according to [1], further comprising 0.1 to 10 mass % of recycled methyl acrylate based on 100 mass % of the monomer composition. [3] The methyl methacrylate copolymer composition for injection molding according to [1] or [2], further comprising 0.1 to 10 mass % of non-recycled methyl acrylate based on 100 mass % of the monomer composition. [4] A material for injection molding, comprising the methyl methacrylate copolymer composition for injection molding according to any one of [1] to [3]. [5] A material for molding a tail lamp part, comprising the methyl methacrylate copolymer composition for injection molding according to any one of [1] to [3]. Effect of the Invention

[0007] According to the present invention, a methyl methacrylate copolymer composition for injection molding can be provided which can prevent polymerization stall even when recycled methyl methacrylate is used, and further can suppress the occurrence of silver streaks during injection molding. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a graph showing the temperature trend during polymerization in Example 1. [Diagram 2] FIG. 2 is a graph showing the temperature trend during polymerization in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention (hereinafter, referred to as the present embodiment) will be described in detail. The present invention is not limited to the following embodiment, and can be modified in various ways within the scope of the present invention.

[0010] The methyl methacrylate copolymer composition for injection molding of the present embodiment is a methyl methacrylate copolymer composition containing a methyl methacrylate copolymer obtained by polymerizing a monomer composition containing 10 to 50 mass% recycled methyl methacrylate and 50 to 90 mass% non-recycled methyl methacrylate, wherein the content of methyl isobutyrate in 100 mass% of the methyl methacrylate copolymer composition is 1 to 1500 mass ppm, and the content of 2-heptene and / or 3-heptene in 100 mass% of the methyl methacrylate copolymer composition is 10 to 2000 mass ppm.

[0011] In this specification, "recycled methyl methacrylate" and "recycled methyl acrylate" refer to methyl methacrylate or methyl acrylate obtained by decomposing and purifying a polymer containing methyl methacrylate units (e.g., polymethyl methacrylate, copolymers containing methyl methacrylate units), a polymer containing methyl acrylate units (e.g., polymethyl acrylate, copolymers containing methyl acrylate units), a polymer blend containing polymethyl methacrylate and / or polymethyl acrylate, or the like. In this specification, "non-recycled methyl methacrylate" and "non-recycled methyl acrylate" refer to methyl methacrylate and methyl acrylate produced using raw materials produced from petroleum, coal, natural gas, shale oil, biomass methanol, etc. Examples include virgin methyl methacrylate and virgin methyl acrylate, and do not include recycled monomers. In this specification, the term "methyl methacrylate copolymer" refers to a copolymer containing 80% by mass or more of methyl methacrylate monomer units and recycled methyl methacrylate monomer units as monomer units relative to 100% by mass of the monomer units contained in the copolymer. For example, a homopolymer containing 100% by mass of methyl methacrylate monomer units is also included in the methyl methacrylate copolymer. In this specification, the term "monomer composition" refers to a mixture of monomer components, and a composition containing 80 mass % or more in total of recycled methyl methacrylate and non-recycled methyl methacrylate. In this specification, the term "methyl methacrylate copolymer composition" refers to a composition containing 90% by mass or more of the above-mentioned "methyl methacrylate copolymer" relative to 100% by mass of the composition.

[0012] The monomer composition contains 10 to 50% by mass of recycled methyl methacrylate and 50 to 90% by mass of non-recycled methyl methacrylate relative to 100% by mass of the monomer composition. The monomer composition may further contain recycled methyl acrylate, non-recycled methyl acrylate, and other monomers. The total mass ratio of recycled methyl methacrylate and non-recycled methyl methacrylate relative to 100% by mass of the monomer composition is preferably 80% by mass or more, more preferably 90% by mass or more. The total mass ratio of recycled methyl methacrylate, non-recycled methyl methacrylate, recycled methyl acrylate, and non-recycled methyl acrylate relative to 100% by mass of the monomer composition is preferably 90% by mass or more, more preferably 95% by mass or more, and particularly preferably 100% by mass.

[0013] If the recycled methyl methacrylate content is less than 10% by mass, the amount of recycled materials used will be low, resulting in a small contribution to the environment.If the recycled methyl methacrylate content exceeds 50% by mass, the amount of impurities derived from recycled materials will increase, making it difficult to prevent the Trommsdorff effect from slowing down. The lower limit of the recycled methyl methacrylate is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more. The upper limit of the recycled methyl methacrylate is preferably 45% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less.

[0014] If the non-recycled methyl methacrylate is less than 50% by mass, the amount of impurities derived from recycled products increases and it becomes difficult to prevent the Trommsdorff effect from slowing down.If the non-recycled methyl methacrylate is more than 90% by mass, the amount of recycled products used is low and the contribution to the environment is small. The lower limit of non-recycled methyl methacrylate is preferably 55% by mass or more, more preferably 60% by mass or more, and even more preferably 65% ​​by mass or more. The upper limit of recycled methyl methacrylate is preferably 85% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less.

[0015] In the recycled methyl methacrylate, methyl isobutyrate is often contained in an amount of about 100 to 50,000 ppm by mass. In the present embodiment, it is preferable to adjust the content of methyl isobutyrate by removing methyl isobutyrate by distillation or obtaining a copolymer by suspension polymerization. The content of methyl isobutyrate in 100% by mass of the recycled methyl methacrylate copolymer composition is 1 to 1500 ppm by mass. The presence of a predetermined amount of methyl isobutyrate can suppress silver streaks during injection molding. If the content exceeds 1500 ppm, heat resistance may deteriorate, which is not preferable. The lower limit is preferably 2 ppm or more, more preferably 3 ppm or more, and even more preferably 5 ppm or more. The upper limit is preferably 1000 ppm or less, more preferably 500 ppm or less, and even more preferably 200 ppm or less.

[0016] The content of 2-heptene and / or 3-heptene in 100% by mass of the recycled methyl methacrylate copolymer composition (i.e., the three contents of the content of 2-heptene, the content of 3-heptene, and the total content of 2-heptene and 3-heptene) is 10 to 2000 ppm by mass. The content of 2-heptene and / or 3-heptene is preferably the total content of 2-heptene and 3-heptene. When recycled methyl methacrylate is included in the monomer composition, polymerization can be performed so that a predetermined amount of 2-heptene and / or 3-heptene is included in the copolymer to prevent the polymerization from stalling. 2-heptene and / or 3-heptene may be dissolved in the monomer and contained therein, or may be generated as a decomposition product of the initiator. The lower limit is preferably 50 ppm or more, more preferably 100 ppm or more, and even more preferably 200 ppm or more. The upper limit is preferably 1800 ppm or less, more preferably 1600 ppm or less, and further preferably 1400 ppm or less.

[0017] It is preferable that the monomer composition further contains 0.1 to 10 mass% of recycled methyl acrylate in 100 mass%. Recycled methyl methacrylate may contain recycled methyl acrylate as an impurity, and it is preferable to polymerize the monomer composition containing a certain amount of recycled methyl acrylate, which is energy efficient. If the amount of recycled methyl acrylate exceeds 10 mass%, the amount of impurities increases and the heat resistance may deteriorate, which is not preferable. The lower limit is preferably 0.5 mass% or more, more preferably 1 mass% or more, and even more preferably 1.5 mass% or more. The upper limit is preferably 9.5 mass% or less, more preferably 9 mass% or less, and even more preferably 8.5 mass% or less.

[0018] It is preferable to further contain 0 to 10% by mass of non-recycled methyl acrylate in 100% by mass of the above monomer composition, and more preferably 0.1 to 10% by mass. By containing non-recycled methyl acrylate, thermal decomposition resistance can be improved. If it is contained in excess of 10% by mass, heat resistance may deteriorate, which is not preferable. The lower limit is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 1.5% by mass or more. The upper limit is preferably 9.5% by mass or less, more preferably 9% by mass or less, and even more preferably 8.5% by mass or less.

[0019] The methyl methacrylate copolymer may further contain other monomer units, such as other vinyl monomer units, that are copolymerizable with methyl methacrylate.

[0020] The other monomer may be a vinyl monomer copolymerizable with methyl methacrylate, and specific examples thereof include alkyl methacrylates having an alkyl group with 2 to 18 carbon atoms; alkyl acrylates having an alkyl group with 2 to 18 carbon atoms; α,β-unsaturated acids such as acrylic acid and methacrylic acid; unsaturated group-containing divalent carboxylic acids and alkyl esters thereof such as maleic acid, fumaric acid, and itaconic acid; aromatic vinyl compounds such as styrene, α-methylstyrene, and styrene having a substituent on the benzene ring; cyanide vinyl compounds such as acrylonitrile and methacrylonitrile; maleic anhydride, maleimide, and N-substituted maleimide; ethylene glycol di(meth)acrylate, diethylene glycol Examples of the ester include those in which both terminal hydroxyl groups of ethylene glycol or its oligomers are esterified with acrylic acid or methacrylic acid, such as triethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate; those in which hydroxyl groups of two alcohols are esterified with acrylic acid or methacrylic acid, such as neopentyl glycol di(meth)acrylate and di(meth)acrylate; those in which polyhydric alcohol derivatives, such as trimethylolpropane and pentaerythritol, are esterified with acrylic acid or methacrylic acid; and polyfunctional monomers, such as divinylbenzene. These can be used alone or in combination of two or more types.

[0021] <Polymerization method> The methyl methacrylate copolymer can be produced, for example, by using a monomer composition containing a monomer constituting the methyl methacrylate copolymer, a polymerization initiator, a chain transfer agent, a suspending agent, other additives, and the like.

[0022] As the polymerization initiator, when free radical polymerization is used, peroxide-based initiators such as di-t-butyl peroxide, dilauroyl peroxide, t-butylperoxy 2-ethylhexanoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, t-hexylperoxy 2-ethylhexanoate, 1,1,3,3,-tetramethylbutylperoxy 2-ethylhexanoate, and t-amylperoxy 2-ethylhexanoate, and azo-based initiators such as azobisisobutyronitrile, azobisisovaleronitrile, and 1,1-azobis(1-cyclohexanecarbonitrile) can be used, which can be used alone or in combination of two or more kinds. These radical initiators can be combined with a suitable reducing agent to be used as a redox-based initiator. Of these, t-hexylperoxy 2-ethylhexanoate and 1,1,3,3-tetramethylbutylperoxy 2-ethylhexanoate are preferred.

[0023] The polymerization initiator is generally used in an amount of 0.001 to 1% by mass relative to 100% by mass of the total mass of the monomers.

[0024] In the method for producing the methyl methacrylate copolymer, when the copolymer is produced by radical polymerization, a commonly used chain transfer agent can be used to adjust the molecular weight.

[0025] As the chain transfer agent, for example, mercaptans such as n-butyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, 2-ethylhexyl thioglycolate, ethylene glycol dithioglycolate, trimethylolpropane tristhioglycolate, and pentaerythritol tetrakis(thioglycolate) are preferably used.

[0026] The chain transfer agent may be used in an amount of 0.001 to 1% by mass relative to 100% by mass of the total mass of the monomers. The amount of the chain transfer agent is determined depending on the desired molecular weight.

[0027] The polymerization method for the methyl methacrylate copolymer is preferably suspension polymerization or emulsion polymerization. By carrying out the polymerization in water, the content of methyl isobutyrate can be optimized.

[0028] (Additives) The methyl methacrylate copolymer composition of the present embodiment may optionally contain other additives. The additives are not particularly limited as long as they can exert the effects of the present invention, and may be appropriately selected depending on the purpose.

[0029] Examples of additives include, but are not limited to, ultraviolet absorbers, heat stabilizers, light stabilizers, plasticizers, flame retardants, flame retardant assistants, curing agents, curing accelerators, antistatic agents, conductivity imparting agents, stress relaxation agents, mold release agents, crystallization accelerators, hydrolysis inhibitors, lubricants, impact imparting agents, sliding property improvers, compatibilizers, nucleating agents, reinforcing agents, flow adjusters, dyes, sensitizers, colorants, anti-settling agents, anti-sagging agents, fillers, anti-foaming agents, light diffusing fine particles, rust inhibitors, antibacterial agents, anti-fungal agents, anti-fouling agents, conductive polymers, and the like.

[0030] The methyl methacrylate copolymer composition of the present embodiment is for injection molding. By optimizing the polymerization composition, it is possible to obtain effects such as suppression of silver streaks during injection molding.

[0031] The methyl methacrylate copolymer composition for injection molding of the present embodiment is preferably used for tail lamps. By recovering methacrylic resin from tail lamps, thermally decomposing it to generate methyl methacrylate, producing the methyl methacrylate copolymer composition of the present embodiment, and using it again for tail lamps, a closed cycle can be turned, and the contribution to the environment can be maximized.

[0032] (Properties of Methyl Methacrylate Copolymer Composition) <Heat resistance> As an index of heat resistance, the Vicat softening temperature can be used. From the viewpoint of heat resistance during actual use, the Vicat softening temperature of the methyl methacrylate copolymer composition of the present embodiment is preferably 100° C. or higher, more preferably 105° C. or higher. The Vicat softening temperature can be measured by the method described in the examples below.

[0033] The injection molding material of the present embodiment includes the above-mentioned methyl methacrylate copolymer composition for injection molding of the present embodiment, and may be composed only of the methyl methacrylate copolymer composition for injection molding. The injection molding material can be used as a material for injection molding. The tail lamp part molding material of the present embodiment includes the above-mentioned methyl methacrylate copolymer composition for injection molding of the present embodiment, and may be composed only of the methyl methacrylate copolymer composition for injection molding of the present embodiment. The tail lamp part molding material can be used as a material for injection molding of table lamp parts.

[0034] (Method for producing methyl methacrylate copolymer composition pellets) The pellets of the methyl methacrylate copolymer composition of the present embodiment can be produced by melt-kneading the above-mentioned methyl methacrylate copolymer composition, and, if necessary, a rubber polymer, another resin other than the methyl methacrylate copolymer composition, and an additive. Examples of a method for producing methyl methacrylate copolymer composition pellets include a method of kneading using a kneading machine such as an extruder, a heating roll, a kneader, a roller mixer, a Banbury mixer, etc. Among these, kneading using an extruder is preferred from the viewpoint of productivity. The kneading temperature may be in accordance with the preferred processing temperatures of the polymers constituting the methyl methacrylate copolymer composition and other resins to be mixed, and is generally in the range of 140 to 300°C, preferably 180 to 280°C. It is also preferable to provide the extruder with a vent port in order to reduce volatile content.

[0035] [Molded body] The molded article of the present embodiment is a molded article containing the methyl methacrylate copolymer composition of the present embodiment described above. The molded article of the present embodiment is suitably used as an optical component such as a light guide plate or a light guide, or a vehicle component. The thickness of the molded article of this embodiment is preferably 0.01 to 10 mm, and may be 0.01 to 1 mm, from the viewpoint of excellent handleability and strength, and also from the viewpoint of excellent optical properties when the molded article of this embodiment is used as an optical component. From the viewpoint of suppressing birefringence, the thickness is more preferably 8 mm or less, further preferably 5 mm or less, even more preferably 3 mm or less, and further more preferably 2 mm or less. When used as an injection molded article, the thickness is preferably 0.02 mm or more, and more preferably 0.05 mm or more.

[0036] When the molded article of this embodiment is a vehicle component, the thickness of the molded article is preferably 0.03 to 3 mm, more preferably 0.5 to 3 mm, and even more preferably 0.8 to 2.8 mm, from the viewpoints of weight reduction, strength, and moldability. EXAMPLES

[0037] The present invention will be described more specifically with reference to the following examples and comparative examples. <Raw materials> The raw materials used were as follows: · Recycled methyl methacrylate (recycled MMA) Asahi Kasei Delpet 80N is pyrolyzed at 400°C in a twin-screw extruder to obtain crude monomer, which is then distilled and purified to obtain methyl methacrylate containing 2.5 ppm by mass of 2,4-dimethyl-6-t-butylphenol. · Recycled methyl acrylate (recycled MA) Methyl acrylate obtained during the distillation and purification of the above-mentioned raw monomer contains 15 ppm of 4-methoxyphenol. Methyl methacrylate (MMA) Manufactured by Asahi Kasei (containing 2.5 ppm by mass of 2,4-dimethyl-6-t-butylphenol manufactured by Chugai Boeki as a polymerization inhibitor) Methyl acrylate (MA) Manufactured by Mitsubishi Chemical (contains 15 ppm of 4-methoxyphenol as a polymerization inhibitor) n-Octyl mercaptan (NOM) manufactured by Arkema t-Butyl peroxy 2-ethylhexanoate (Perbutyl O): Made by Nippon Oil & Fats t-Hexylperoxy 2-ethylhexanoate (Perhexyl O): Made by Nippon Oil & Fats 1,1,3,3,-Tetramethylbutylperoxy 2-ethylhexanoate (Perocta O): Made by Nippon Oil & Fats t-Amylperoxy 2-ethylhexanoate (Luperox 575): Arkema Yoshitomi Dilauryl peroxide (LPO): Made by Nippon Oil & Fats

[0038] Example 1 -Adjustment of suspension agent- 5 kg of water, 130 g of aluminum hydroxide having an average particle size of 33 μm, 0.39 g of sodium lauryl sulfate, and 2.3 g of EDTA were added to a vessel equipped with a stirrer equipped with four inclined paddle blades and mixed to obtain a mixed liquid (a1). The average particle size of the suspension in the mixed liquid (a1) was 33 μm, and the pH of the obtained mixed liquid (a1) was 5.5. The obtained mixed liquid (a1) was heated to 70°C. -Polymerization reaction- Next, 25 kg of water was added to a 60L reactor and the temperature was raised to 80°C, and the raw material was added to the reactor, which was a mixture of 3 kg of the mixed liquid (a1) and 21 kg of the monomer components of the formulation shown in Table 1, mixed with a polymerization initiator and a chain transfer agent. Then, the temperature was kept at about 80°C to carry out suspension polymerization, and a peak of heat generation due to the Trommsdorff effect was observed about 120 minutes after the raw material was added. Then, the temperature was raised to 90°C at a rate of 1°C / min, and the temperature was kept at about 90°C or higher for 45 minutes, and the polymerization reaction was essentially terminated to obtain a polymer slurry. Next, the obtained polymer slurry was cooled to 50°C. 20% by mass of sulfuric acid was added to the polymer slurry to dissolve the suspending agent, and a polymerization reaction solution was obtained. Next, the obtained polymerization reaction solution was sieved through a 1.68 mm mesh sieve to remove aggregates, filtered, and separated into bead-like methyl methacrylate copolymer particles and suspension waste liquid. The temperature trend at this time is shown in Figure 1. -Cleaning process- Then, an approximately equal amount of ion-exchanged water at about 70°C was added to the bead-shaped methyl methacrylate copolymer particles, and the mixture was stirred, washed, and filtered. The mixture was washed once more with ion-exchanged water at about 70°C (a total of two water washes) to obtain a slurry polymer solution. A sodium hydroxide aqueous solution was added dropwise to the obtained slurry polymer solution to adjust the pH to 8.5, and the mixture was stirred and washed. The slurry polymer solution was filtered, and ion-exchanged water at 70°C was added and stirred to wash the mixture. The slurry polymer solution was then filtered to obtain copolymer beads. The obtained copolymer beads were dried overnight in an oven at 70°C to obtain methyl methacrylate copolymer beads. The weight average molecular weight of the obtained methyl methacrylate copolymer beads was 105,000, and Mw / Mn=1.9.

[0039] (Examples 2 to 4, 6 to 12, Reference Example 1, Comparative Examples 1 and 2) A methyl methacrylate copolymer was obtained in the same manner as in Example 1, except that the raw material composition was changed to the blend shown in Table 1. In Comparative Examples 1 and 2, no exothermic peak due to the Trommsdorff effect was observed. The temperature trend during polymerization in Comparative Example 1 is shown in FIG.

[0040] Example 5 Methyl methacrylate copolymer beads were obtained in the same manner as in Example 1, except that the raw material composition was as shown in Table 1 and 2000 ppm by mass of methyl isobutyrate was further added to the monomers for polymerization.

[0041] Comparative Example 3 Methyl methacrylate copolymer beads were obtained in the same manner as in Example 1, except that the raw material composition was as shown in Table 1 and 5,000 ppm by mass of methyl isobutyrate was further added to the monomers for polymerization.

[0042] Comparative Example 4 Methyl methacrylate copolymer beads were obtained in the same manner as in Example 1, except that the raw material composition was as shown in Table 1 and 0.3 parts by mass of 2-heptene was further added to the monomers and polymerized.

[0043] [The Tromsdorff effect stalls] In the above polymerization, the cases where a heat generation peak due to the Trommsdorff effect was observed (the cases where a rapid rise in the temperature in the system occurred in the latter stage of the polymerization, and the temperature in the system rose by 1°C or more (for example, the temperature in the system rose by 1°C or more per 5 minutes)) were rated as ◯ (good), and the cases where a heat generation peak due to the Trommsdorff effect was not observed were rated as × (bad).

[0044] [Physical properties of methyl methacrylate copolymer] (Weight average molecular weight, molecular weight distribution) The weight average molecular weight and molecular weight distribution of the methyl methacrylate copolymer beads obtained in the Examples and Comparative Examples were measured using the following apparatus and conditions. Measurement device: gel permeation chromatography (HLC-8320GPC) manufactured by Tosoh Corporation. Column: one TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 were used, connected in series in this order. In this column, high molecular weight compounds elute early, while low molecular weight compounds elute late. Detector: RI (differential refractometer) detector Detection sensitivity: 3.0mV / min Column temperature: 40℃ Sample: 0.02 g of methyl methacrylate copolymer beads in 20 mL of tetrahydrofuran Injection volume: 10μL Developing solvent: tetrahydrofuran, flow rate: 0.6 mL / min 2,6-di-t-butyl-4-methylphenol (BHT) was added at 0.1 g / L as an internal standard. As standard samples for the calibration curve, the following ten types of polymethyl methacrylate (PMMA Calibration Kit MM-10, manufactured by Polymer Laboratories) with different molecular weights and known monodisperse peak top molecular weights were used. Peak top molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard material 10 850 Under the above conditions, the RI detection intensity was measured versus the elution time of the methyl methacrylate copolymer. The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the methyl methacrylate copolymer were determined based on the area in the GPC elution curve and the calibration curve of a third-order approximation equation.

[0045] [Measurement of residual monomer amount] The amount of residual monomer in the obtained methyl methacrylate copolymer beads was measured using a Shimadzu gas chromatograph GC-2010+ (FID) under the following column and conditions. The mass ratio (mass%) of the residual methyl methacrylate monomer to 100 mass% of the methyl methacrylate copolymer is shown in Table 1. Test conditions Column used: TC-1 (non-polar) φ0.32mm x 30m x 0.25μm Carrier gas: Nitrogen 1.3mL / min Setting temperature: INJ / DET=230℃ / 300℃ Sample: 0.3 g of methyl methacrylate copolymer beads dissolved in 25 mL of chloroform Holding time: 15min

[0046] [Silver Streaks] The appearance of the molded product can be evaluated based on, for example, the presence or absence of bubbles, streaks, silver streaks, etc., and specifically, it can be evaluated by the following method. When the methyl methacrylate copolymer composition for injection molding of this embodiment is made into an injection molded article, after drying at 80°C for 24 hours, 50 test pieces are molded using an injection molding machine and a measuring mold, and the number of test pieces showing silver streaks on the surface of the test pieces is preferably 10 or less, more preferably 5 or less, and even more preferably 2 or less. The presence or absence of silver streaks in the molded product can be evaluated by the following method. The methyl methacrylate copolymer beads obtained in the Examples and Comparative Examples were fed into a twin-screw extruder having a diameter of 26 mm, melt-kneaded (compounded) to form strands, and the strands were cooled in a water bath and then cut into pellets using a pelletizer. During compounding, a vacuum line was connected to the vent of the extruder, and volatile components such as moisture and monomer components were removed under conditions of -0.06 MPa. The resin temperature during compounding was 250 to 270°C. The methyl methacrylate copolymer pellets obtained by the above method were dried at 80° C. for 24 hours, and then evaluated for the presence or absence of silver streaks using the injection molding machine, measurement mold, and molding conditions described below. Specifically, resin was injected into the center of the mold surface under the following conditions, and 40 seconds after the end of injection, the spiral molded product was removed and evaluated for the occurrence of silver streaks. After switching the resin, 20 shots were discarded, and the evaluation was carried out using 50 pieces from the 21st to 70th shots. Injection molding machine: EC-100SX (Toshiba Machine Co., Ltd.) Measurement mold: A mold with a groove 2 mm deep and 12.7 mm wide carved into the surface in the shape of an Archimedes spiral from the center of the surface. Molding conditions Resin temperature: 290℃ Mold temperature: 70℃ Maximum injection pressure: 75MPa Injection time: 20sec Evaluation with or without Silver Streaks A: Silver streaks were observed in 2 or fewer samples out of 50. B: Silver streaks were observed in 5 or fewer samples out of 50. C: 10 or fewer samples out of 50 had silver streaks D: More than 10 out of 50 samples had silver streaks.

[0047] [Heat decomposition resistance] (a) Temperature at 1% weight loss Measurements were carried out using the methyl methacrylate copolymer compositions obtained in the Examples and Comparative Examples under the following equipment and conditions. The temperature at which the weight of the composition was reduced by 1% was calculated and defined as the thermal decomposition onset temperature (temperature at which the weight was reduced by 1%) (°C). Measurement equipment: Differential thermobalance Thermo plus EVO II TG8120, manufactured by Rigaku Corporation Sample size: approx. 10 mg Measurement atmosphere: Nitrogen (100mL / min) Measurement conditions: The material was held at 100°C for 5 minutes, and then heated to 400°C at a rate of 10°C / min. The point at which 1% weight loss occurred was defined as the thermal decomposition onset temperature (1% weight loss temperature). Measurement equipment: Differential thermobalance Thermo plus EVO II TG8120 (manufactured by Rigaku Corporation) Sample amount: Approximately 10 mg Measurement atmosphere: Nitrogen (100mL / min) Measurement conditions: held at 50°C for 2 minutes, heated to 200°C at 20°C / min, heated to 250°C at 20°C / min, heated to the set temperature of 284°C at 10°C / min, held at 284°C for 60 minutes, and calculated the weight loss rate (%) 30 minutes after the start of holding. The measured temperature when the set temperature was 284°C was approximately 290°C. Thermal decomposition resistance evaluation A: 1% weight loss temperature is 300℃ or higher B: 1% weight loss temperature is 280℃ or higher and less than 300℃ C: 1% weight loss temperature is less than 280℃

[0048] <Heat resistance> (VICAT softening temperature) In accordance with ISO 306 B50, 4 mm thick test pieces were molded using the methyl methacrylate copolymer composition pellets obtained in the examples and comparative examples, and the VICAT softening temperature (°C) was measured and used as an index for evaluating heat resistance. A: VICAT softening temperature (℃) is 110℃ or higher B: VICAT softening temperature (℃) is 100℃ or higher but less than 110℃ C: VICAT softening temperature (℃) is 90℃ or higher but less than 100℃

[0049] [Table 1]

[0050] Comparing Example 1 with Comparative Example 1, it is found that as the amount of recycled methyl methacrylate increases, the Tormsdorff effect stalls and the physical properties of the molded product deteriorate. Comparing Example 2 with Comparative Example 2, it is found that the Tormsdorff effect is expressed by using an initiator that generates 2-heptene and / or 3-heptene as a decomposition product when recycled methyl methacrylate is used. Comparing Example 2 with Comparative Examples 3 and 4, it is found that the thermal decomposition resistance and thermal stability deteriorate when the content of methyl isobutyrate and / or 2-heptene and / or 3-heptene becomes too high. [Industrial Applicability]

[0051] According to the present invention, a methyl methacrylate copolymer composition for injection molding can be provided which can prevent polymerization stall and further suppress the occurrence of silver streaks during injection molding even when recycled methyl methacrylate is used.

Claims

1. 10 to 50% by mass of recycled methyl methacrylate, 50 to 90% by weight of non-recycled methyl methacrylate, A methyl methacrylate copolymer composition comprising a methyl methacrylate copolymer obtained by polymerizing a monomer composition containing The content of methyl isobutyrate in the methyl methacrylate copolymer composition is 1 to 1500 ppm by mass, The content of 2-heptene and / or 3-heptene in the methyl methacrylate copolymer composition is 10 to 2000 ppm by mass. Methyl methacrylate copolymer composition for injection molding.

2. The methyl methacrylate copolymer composition for injection molding according to claim 1, further comprising 0.1 to 10% by mass of recycled methyl acrylate per 100% by mass of the monomer composition.

3. The methyl methacrylate copolymer composition for injection molding according to claim 1 or 2, further comprising 0.1 to 10 mass% of non-recycled methyl acrylate in 100 mass% of the monomer composition.

4. An injection molding material comprising the methyl methacrylate copolymer composition of claim 1 for injection molding.

5. A material for molding a tail lamp part, comprising the methyl methacrylate copolymer composition for injection molding according to claim 1 .

Citation Information

Patent Citations

  • Process for treating gaseous effluents from the pyrolysis of polymers - Patent Application 20070122997

    JP2022520072A